Biometry of fruits and seeds of Syzygium malaccensis (L) Meer & Perry native in municipality of Capitão Poço, Pará, Brazil - Souza, Nayane da Silva; Silva, Maria Kalyane Farias da; Oliveira, Larissa Jaina da Silva de; Carvalho, Hemerson Doglas Campos; Lima, Ironeide Lima e; Santa Brígida, Marluce Reis Souza (Revista Verde de Agroecologia e Desenvolvimento Sustentável, 2018)
Fruit biometry provides information needed to trigger several studies of economic interest allowing continuous increase rational search and efficient use fruits. Objective of this study was to characterize fruits and seeds individuals native of Syzygium malaccense (L.) Merr & Perry in municipality of Capitão Poço-Pa by means biometric evaluation their physical characteristics. The ripe fruits were harvested last week of August 2016, the end fruiting season in the region, collected 4 different progenies. 200 healthy fruits were selected for established biometric analyzes, being biometric characteristics were evaluated: fruit weight, pulp weight, seed weight, fruit length, fruit width, seed length, seed width, fruit volume in ml. Biometric characteristics of fruits and seeds were analyzed by frequency distribution. Fruits showed variability for all analyzed biometric characteristics. Total yield pulp was directly influenced by weight fruit, as well as size and weight seed. The highest fruits presented values of weight around 68 to 78 g, length and width of 59 to 62 mm and 49 to 54 mm being these results great influence for yield pulp.